Content presentation techniques for learning experience enhancement in Massive Open Online Course (MOOC) / Erny Arniza Ahmad - Ahmad, Erny Arniza (UiTM Press, 2021)
MOOCs (Massive Open Online Courses) are a new and innovative technique of disseminating knowledge to millions of people all over the world. Despite being a fantastic learning tool with a global reach, MOOCs have their own set of restrictions, resulting in an extraordinarily low course completion rate. Personalization and engagement are lacking in traditional material presentation strategies. Hence, MOOCs must adopt advanced learning approaches in order to create a more engaging experience for the learners. This study introduces Augmented MOOC (A-MOOC), an enriched learning MOOC environment. A-MOOC explores Active Learning, Augmented Reality, and Gamification techiques, and show how these strategies can be combined with MOOC content in both online and offline modes. It demonstrates the favourable influence of creating interactive and more engaging content in the current learning setting to increase learners' motivation to complete a MOOC.